Trajectoires et adaptations à une crise multiple: Port-au-Prince depuis le séisme du 12 janvier 2010 au travers des concepts d’exit, voice, loyalty et apathie - Michel Desse; Jean-Philippe Pierre; Georges Eddy Lucien (VertigO, 2012)
The earthquake which struck Port-au-Prince on January 12th 2010, ravaged the town causing the death of 250,000 people, injuring close to a million and leaving hundreds of thousands homeless. The extent of the damage was essentially due to poverty but urban management choices also played a role, both factors causing the poorer segments of the population to relocate in shantytowns. A study of territorial management issues using Albert Otto Hirschman's Exit-Voice-Loyalty model makes comparatively better sense of the survivors' post-cataclysm strategies. The January 12th earthquake caused multiple crises, upsetting Haiti's environmental, healthcare, social, economic and political structures. As a result, attitudes, including spatial strategies, became considerably more individualized, with behavioral patterns ranging from withdrawal and relocation (Exit) to protests (Voice), reciprocated support (Loyalty) and Apathy.